Elevated Neuropeptide Y in Endothelial Dysfunction Promotes Macrophage Infiltration and Smooth Muscle Foam Cell Formation - Choi, Bongkun; Shin, Min-Kyung; Kim, Eun-Young; Park, Ji-Eun; Lee, Halim; Kim, Seong Who; Song, Jae-Kwan; Chang, Eun-Ju (Frontiers in Immunology, 2019)
Abstract Endothelial dysfunction has been linked vascular inflammation and foam cell formation but the underlying mechanisms still remain unclear. We sought to define the factors inducing inflammation and smooth muscle foam cell formation under endothelial dysfunction using endothelial nitric oxide synthase (eNOS)-deficient mice. Vascular smooth muscle cells (VSMCs) from eNOS-deficient mice displayed increased expression of macrophage-related genes and elevated lipid uptake. Neuropeptide Y (NPY) was upregulated in the aorta from the eNOS-deficient mice and promoted macrophage chemotaxis toward VSMCs while enhancing the activity of matrix metalloproteinase-3. Notably, NPY induced lipid uptake in VSMCs, facilitating smooth muscle foam cell formation, in association with enhanced expression of genes related to modified low-density lipoprotein uptake and macrophages. NPY was augmented by inflammatory pentraxin 3 (PTX3) in VSMCs. PTX3 enhanced macrophage migratory capacity through NPY/neuropeptide Y receptor axis and this effect was attenuated by pharmacological inhibition with a receptor-specific antagonist. These observations suggest that endothelial dysfunction leads to the elevation of NPY that amplifies vascular inflammation by increasing inflammatory cell chemotaxis and triggers smooth muscle foam cell formation.